Shibori Skills to Improve Fine Motor Ability of Children with Autism - Elisa Julianti; Fatmawati Fatmawati (Department of Special Education, 2019)
This study aims to improve the fine motor skills of autistic children through shibori skills. Problems that occur in the process of learning skills in SLB Autisma YPPA Padang are students who experience obstacles in fine motor skills such as difficulty, also the learning process that is given by teachers about shibori is less varied due to the lack of teacher knowledge about shibori. Based on this problem, this study was conducted to prove that shibori skills can improve fine motor skills for autistic children. This type of research is classroom action research that uses two cycles. The results of this study prove that shibori skills can improve fine motor skills for autistic children in SLB Autisma YPPA Padang